Cervical Cancer Visual Screening Experience in the Republic of Tajikistan - Nilufar Muhsinzoda; Alex Bingjie Yuan; Rustam Tursunov (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: To study the results of the first pilot study of organized visual cervical cancer (CC) screening for the detection of precancerous pathology of the cervix in two pilot districts of the Republic of Tajikistan.